Physiotherapy treatment approaches for survivors of critical illness: a proposal from a Delphi study. (1st December 2020) - Kwakman, Robin C. H.; Major, Mel E.; Dettling-Ihnenfeldt, Daniela S.; Nollet, Frans; Engelbert, Raoul H. H.; van der Schaaf, Marike
ABSTRACT: Purpose : The aim of this study was to develop practical recommendations for physiotherapy for survivors of critical illness after hospital discharge. Methods : A modified Delphi consensus study was performed. A scoping literature review formed the basis for three Delphi rounds. The first round was used to gather input from the panel to finalize the survey for the next two rounds in which the panel was asked to rank each of the statements on an ordinal scale with the objective to reach consensus. Consensus was defined as a SIQR of ≤ 0.5. Ten Dutch panelists participated in this study: three primary care physiotherapists, four intensive care physiotherapists, one occupational therapist, one ICU-nurse and one former ICU-patient. All involved professionals have treated survivors of critical illness. Our study was performed in parallel with an international Delphi study with hospital-based health-care professionals and researchers. Results : After three Delphi rounds, consensus was reached on 95.5% of the statements. This resulted in practical recommendations for physiotherapy for critical illness survivors in the primary care setting. The panel agreed that the handover should include information on 14 items. Physiotherapy treatment goals should be directed toward improvement of aerobic capacity, physical functioning, activities in daily living, muscle strength, respiratory and pulmonary function, fatigue, pain, and health-related quality of life. Physiotherapy measurements and interventions to improve these outcomes are suggested. Conclusion : This study adds to the knowledge on post-ICU physiotherapy with practical recommendations supporting clinical decision-making in the treatment of survivors of critical illness after hospital discharge.